Rewriting the East: Bridging Past and Present Through Aesthetic Resistance in Pramoedya Ananta Toer’s Child of All Nations (Postcolonial Approach) - Nani Cahyani; B. Venkat Rao; Dana Amirbayeva; Sanaria Maneba; Syahrir (Universitas Islam Negeri Palopo, 2025)
This article revealed the concept of aesthetic resistance in Pramoedya’s Child of All Nations: a shift from a battleground to an intellectual resistance. Explored aesthetic resistance function as a political act in the text of Child of All Nations, and it aimed to reveal the legacies of the oppressive structures that formed the present-day systems. The method employed was descriptive and qualitative, where postcolonial theory served as the analytical lens that framed the colonial epistemologies from past to present. The results finding of this article, Child of All Nations, by Pramoedya Ananta Toer, demonstrates that aesthetic form operates as a mode of resistance. Through narrative style and the act of writing, Minke asserts control over his thoughts and reclaims the authority to define reality. By challenging the colonial narratives imposed upon him, the novel reveals aesthetic resistance to challenging power. Thus, the conclusion of this article is that the aesthetic resistance reclaims narrative authority and rewrites the East from the perspective of postcolonial identity.